Development of a Simple Stirling Engine Demonstration Tool on the Subject of Thermodynamics - Helida, Yeyen; Ching, Chin Peng; Oyewo, Adekunle (Journal of Educational Technology and Learning Creativity, 2023)
Purpose of the study: The aim of this research is to develop a simple Stirling engine teaching aid for the class XI thermodynamics subject at high school and determine students' responses to the teaching aid developed. Methodology: The research method used is research and development (R&D) ADDIE model, namely with the stages of analysis, design, development, implementation, evaluation. The instruments used in this research were media expert validation questionnaires, material expert validation, small group trials and field trials with a Likert scale. The data obtained was then analyzed quantitatively and qualitatively. The test subjects in this research were carried out using small group trials of 10 students and field trials of 30 students from three schools. Main Findings: Based on the results of the material expert validation analysis and media expert validation, an average of 86.5% was obtained which could be categorized as very good, then for small group trials it was obtained 91.9% and 93.1% of field trials could be categorized as very good, so that the media for simple Stirling engine teaching aids were has been developed as a whole very well to be used as a teaching aid in learning in class XI High School. Novelty/Originality of this study: The novelty of developing a simple Stirling engine demonstration tool for the study of thermodynamics lies in its innovative approach to making a complex subject accessible, engaging, and applicable to a wide range of learners, thereby fostering a deeper understanding and appreciation of the field.